Fishing techniques used for the exploitation of fish in the flooded swamp forest of the Lake Tumba micro-basin on the Mbandaka-Center for Research in Ecology and Forestry (CREF Mabali) road axis in Bikoro in the Equateur Province (R.D Congo) - Mondzoi Ndinga, Adrien Boika; Swana, Willy Lusasi; Kilingwa, Clément Munganga; Mutanda, Santos Kavumbu; Kiamfu, Victor Pwema; EyulAnki, Dieudonné Musibono (Acta Aquatica: Aquatic Sciences Journal, 2023)
The objective of this study was to inventory the different fishing techniques used for the exploitation of fish in the flooded swamp forest of the Lake Tumba micro-basin on the Mbandaka-Center for Research in Ecology and Forestry (CREF Mabali) road axis in Bikoro in the Equateur Province of the Democratic Republic of Congo. The exchange-based surveys were carried out using a pre-established survey form to exchange with the fishermen working in the different study sites in order to obtain the expected data. The harvesting of fish was done in a traditional manner using the different fishing gears and techniques used by the fishermen in the study area. The results obtained show that the majority of the fishing practices implemented in this area are not sustainable. In total, ten (10) fishing techniques were identified, among which five (5) easily provide fish, namely, creel fishing, scooping, fishing with ichthyotoxic plants, longline fishing and line fishing, which are the most used by the fishermen. Four fishing techniques (fishing with traditional traps, scooping, fishing with ichthyotoxic plants and fishing by weeding the areas) were considered non-selective and capable of creating an imbalance in the different aquatic ecosystems surveyed. This study contributes to the improvement of the knowledge on the exploitation of the animal biodiversity of the Democratic Republic of Congo, on the one hand, and on the other hand, the perpetuation of the knowledge of the local population whose obsolete character is not in doubt.Keywords: Fishing techniques, Fishing gear, Ichthyological fauna, Bikoro, D.R. Congo